(untitled) (The Pakistan Development Review, 1994)
In the last conference we presented a study on Purchasing Power Parity (PPP) and Real Exchange Rates (RER). One of the conclusions we reached was that a PPP-based measure of the RER did not give sufficient insight into the structural problems underlying disequilibrium situation for Real Exchange Rates. We present a review of recent studies which model the path of Real Exchange Rates determined by sets of determinants. These determinants are usually difficult to quantify and are often represented by proxies. We have reservations about both the choice of some determinants and also appropriativeness of the proxies used to represent them. The purpose of this paper is to critically evaluate frameworks for determining real exchange rates in developing countries. We would suggest a basis for estimation of RER and its equilibrium path.